O upotrebi prezenta u crnogorskoj međuratnoj pripovjedačkoj prozi - Radojević, Danijela (Slavistična revija, 2016)
The paper analyzes the meaning and functions of the use of present tense on the examples from Montenegrin interwar narrative prose, while also specifying the frequency of use of this tense in the examined corpus. Taking into account the theoretical and methodological principles of the indicative and relative present established in the traditional syntactic literature, as well as more recent methodological approaches, the author examines the distinction between present actions. She also considers the criteria of referentiality/non-referentiality. Special attention is paid to tense and modal transpositions of the present tense. Individual examples of use of this tense are also examined from the point of view of their stylistic markedness.
Keywords: 1918-1941; črnogorska književnost; črnogorska proza; črnogorščina; glagol; Montenegrin language; Montenegrin literature; Montenegrin prose; present tense; sedanjik; semantics; semantika; skladnja; syntax; verb